ANALISA DAN IMPLEMENTASI VTP DENGAN ETHERCHANNEL TYPE LACP - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
LAN computer network (Local Area Network) has been widely known since the last decade. However, due to the proliferation of its use, the LAN computer network is changing scalability. This problem can be solved by using Virtual Local Area Network (VLAN) technology. VLANs can address scalability issues and can flexibly reset virtual LAN networks. Especially in the VLAN Trunking Protocol which can minimize the number of switches every time that passes through its VLAN path. So also on the Etherchannel membundle link between switches. In fact a computer network also requires a technology to meet the availability (availability) needs of data traffic. One technology that can meet the availability of data traffic needs is VTP and Etherchannel.